2005
DOI: 10.1016/j.mrgentox.2005.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome analysis in childhood cancer survivors and their offspring—No evidence for radiotherapy-induced persistent genomic instability

Abstract: Suggestions that the induction of genomic instability could play a role in radiation-induced carcinogenesis and heritable disease prompted the investigation of chromosome instability in relation to radiotherapy for childhood cancer. Chromosome analysis of peripheral blood lymphocytes at their first in vitro division was undertaken on 25 adult survivors of childhood cancer treated with radiation, 26 partners who acted as the non-irradiated control group and 43 offspring. A statistically significant increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 38 publications
0
32
0
2
Order By: Relevance
“…14 Most studies report no chromosomal abnormalities, [20][21][22][23][24] malformations, 21,24-28 congenital defects 21 or cancer 29,30 in offspring of cancer survivors, with the exceptions of Dalberg et al 15 who noted an increased risk of malformation among women who conceived after treatment for breast cancer, Winther et al 28 who noted a small (not significantly increased) risk of malformations in children with a parent who received irradiation for childhood cancer and Stahl et al 27 who observed statistically significant but modestly increased risk of major congenital abnormalities among offspring of males with a history of cancer. In accordance with these previous publications, we observed an increased mortality risk in offspring of survivors of hematological cancer, a substantial part of whom will have received radiation therapy for (non) Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…14 Most studies report no chromosomal abnormalities, [20][21][22][23][24] malformations, 21,24-28 congenital defects 21 or cancer 29,30 in offspring of cancer survivors, with the exceptions of Dalberg et al 15 who noted an increased risk of malformation among women who conceived after treatment for breast cancer, Winther et al 28 who noted a small (not significantly increased) risk of malformations in children with a parent who received irradiation for childhood cancer and Stahl et al 27 who observed statistically significant but modestly increased risk of major congenital abnormalities among offspring of males with a history of cancer. In accordance with these previous publications, we observed an increased mortality risk in offspring of survivors of hematological cancer, a substantial part of whom will have received radiation therapy for (non) Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…It should however be stressed that, to date, the issue of cancer predisposition among the nonexposed offspring of irradiated laboratory animals remains highly controversial (reviewed by Dubrova, 2003). Furthermore, it should be stressed that, to date, there has been little experimental evidence for transgenerational effects in humans, with some data showing the lack of chromosomal instability among the children of irradiated childhood cancer survivors (Tawn et al, 2005). Future work should address these important issues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased mortality was related to single treatment course of X-rays because of this diseases (Smith & Doll, 1982). However, other studies performed in adults many years after radiotherapy in childhood haven't shown genetic instability (Tawn et al, 2005). Neither was it shown in persons having professional contact with radiation, who have suffered internal plutonium contamination at least 10 years previous to the study (Whitehouse and Tawn, 2001).…”
Section: The Potential Clinical Consequences Of Radiation Induced Bysmentioning
confidence: 99%